PERUBAHAN GARIS PANTAI DI WILAYAH PESISIR PERAIRAN CISADANE, PROVINSI BANTEN - Tarigan, M Salam (UI Scholars Hub, 2007)
Observation and Change Analysis of Coastline in the Cisadane Coast, Banten Province. The observation of coastline in the Cisadane coastal waters, Banten Province from Tanjung Pasir to Rawa Saban were carried out in July, 2005 and November, 2005. Based on the results of observation coastline in the year of 2005 and over lay with the results of coastline digitation analysis from image landsat 5 TM in the year 1997, we found several abration and acration areas, which may be due to the effects of human activities and natural fenomena such as, hight current and hight wave during moonson over that area.